The application of aeronautical decision-making support systems for improving pilots' performance in flight operations - Li, Wen-Chin; Li, Lun-Wen; Harris, Don; Hsu, Yueh-Ling (Aeronautical and Astronautical Society of the Republic of China, 2014)
Operating a high-technology commercial airliner is not only an issue in psychomotor skill performance but also of a real-time decision-making involving situation awareness and risk management within a limited-time condition. The number of aircraft accidents attributable solely to mechanical failures has decreased markedly in recent years, but the contribution of human error has declined at a much slower rate. Previous research demonstrated a belief rule-based decision support system has provided more reliable and informative performance after training. The purpose of this research was to identify the best mnemonic-based method of decision support systems for improving commercial pilot's performance in the advanced cockpit. A total of 157 airline pilots, all qualified on the Boeing 747-400 evaluated the suitability of four different ADM methods: SHOR (Stimuli, Hypotheses, Options, Response); PASS (Problem identification, Acquire information, Survey strategy, Select strategy); FORDEC (Facts, Options, Risks & Benefits, Decision, Execution, Check); and DESIDE (Detect, Estimate, Set safety objectives, Identify, Do, Evaluate). Each was evaluated for six different types of decisions: go/no go; recognition-primed; response selection; resource management; non-diagnostic procedural; and creative problem-solving. Pilots regarded the FORDEC methodology as being the best in all decision-making scenarios, irrespective of the time available to make the decision. It was also rated as the best ADM method for promoting crew coordination. However, it was advised that practicing the FORDEC mnemonic in flight simulator was important before attempting to apply it in a real life situation.
Keywords: Aeronautical Decision-making; Human Factors in Aviation; Mnemonic-based Training; Situational Awareness